2016
DOI: 10.1007/s00163-016-0244-1
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the influence of product perception and geometric features

Abstract: Research in emotional design and kansei engineering has shown that aesthetics play a significant role in the appeal of a product. This paper contributes to establishing a methodology to identify the relationships between: perceptions, aesthetic features, desire to own and background of consumers. Surveys were conducted with 71 participants to gather their perceptions of 11 vase concepts. Advanced statistical analyses, including mixed models, were applied to allow generalisation of the results beyond the data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…The functionality of a product satisfies customer needs through problem solving and prevention while the aesthetics of a product produce experiential pleasures through viewing, sense of ownership, interaction or consumption (Rahman et al, 2010). Perez Mata et al (2017) indicated that aesthetic appeal is now used to provide consumers with additional value, in a competitive market of products with similar functionality. Also, Orsborn et al (2009) claimed aesthetics are a crucial factor in consumers' buying decision and satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…The functionality of a product satisfies customer needs through problem solving and prevention while the aesthetics of a product produce experiential pleasures through viewing, sense of ownership, interaction or consumption (Rahman et al, 2010). Perez Mata et al (2017) indicated that aesthetic appeal is now used to provide consumers with additional value, in a competitive market of products with similar functionality. Also, Orsborn et al (2009) claimed aesthetics are a crucial factor in consumers' buying decision and satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…We react most emotionally towards those products that fulfill or obstruct our goals (Desmet, 2012) and every act of interaction has the possibility of creating an emotional response. This emotion is being increasingly applied to a design context as it has become clear that "not considering these emotions in the design process is a missed opportunity" (Desmet, 2012); research by Perez Mata et al (2017) already explores the need to identify and target an emotive response from a product, linking this to a person's "desire to own" a product. The design of emotion within products is increasingly part of the growing set of tools that designers need to understand in order to keep up with market trends as the goal of ID shifts to creating an emotional story and experience, not just an artefact (Crossley, in McDonagh et al, 2004).…”
Section: Designing With Emotion 2cmentioning
confidence: 99%
“…Emotions can be seen as "conscious experiences that constitute evaluations of external stimuli" responding to the physical body (Perez Mata et al, 2017), the nature of this means that emotion "tints all human experience" (Tuan, 1977). Emotional range is widely well understood within the "Western stereotypes" (Feldman- Barrett, (2020), as cited in Hammond, 2020) of the popular six "Universal Emotions" by Paul Ekman (Ekman, 1992); those being fear, sadness, anger, happiness, surprise and disgust.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations